Recovery of Sulfur from the Residues of the Chemical Method for the Purification of Sulfur from the Farsch Mine in the Al-Mishraq Mine - Sulav S. Shareef; Thaeir A. Halo; Mote’a O. Abdulla (Iraqi Journal of Industrial Research, 2023)
This research aims to recover sulfur from sulfur residues of the chemical method for purifying mine sulfur in the Al-Mishraq mine by studying and using thermal and air-thermal treatment with a temperature range of 130-190 oC and an increase of 10 degrees for each treatment. After being prepared in the sulfur residues (foam) by grinding it to 200 mesh and chemically analyzing it, we find that it contains a high percentage of elemental sulfur, amounting to 89.60% wt. As for its X-ray diffraction, it was found that the crystal structure of elemental sulfur is of an orthorhombic And after the completion of the two thermal and air-thermal treatments, then the extraction of the carbon-sulfur materials by using a 20% NaOH solution and analyzing them by FESEM, it was found that they have nanostructures and their granular size increased three times than the carbon-sulfur materials extracted from the untreated sulfur residue, and that they have a composition and crystal structure similar to graphite doped with sulfur. The industrial sulfur was filtered in a manner similar to the industrial method of sulfur production units, and 75% wt. of sulfur residues was recovered, and it was in conformity with the Iraqi standard specification 2199 of 2002.